Interfirm differences in scale economies and the evolution of market shares - Makadok, Richard (Strategic Management Journal, 1999)
Evolutionary and resource-based theories imply that firms in an industry with different resources and capabilities may differ in critical characteristics of their production functions, such as economies of scale. This paper measures these inter-firm differences in economies of scale and examines how they affect the subsequent evolution of the market share distribution in the money market mutual fund industry. The findings indicate that fund families with larger marginal benefits to increasing their scale do subsequently gain market share at the expense of their rivals, but that this effect diminishes as the fund family ages, perhaps as a consequence of imitation. Copyright © 1999 John Wiley & Sons, Ltd.